How Work Motivation Mediates the Relationship Between Leadership and Employee Morale - I Komang Oka Permadi; I Kadek Bagiana; Ni Kadek Nonik Rasminingsih (AIBPM Publisher, 2022)
A good leader is a leader who understands the needs and desires of his subordinates, because the survival of the industry depends on employees who act as the driving force and carry out industrial activities. The purpose of this research is to confirm and re-examine the impact of leadership on employee morale, using work motivation as a mediating variable. This study used a non-probability sampling method with a saturation sampling technique (census), in which the total population is sampled as many as 32 people. Path analysis is used in the research to test hypotheses, and SmartPLS version 3.2.9 is used to test the data obtained in this study. The results showed that leadership is a determining factor in increasing work motivation and employee morale. In contrast to work motivation, which is not able to have an effect on employee morale and has not been able to mediate the impact of leadership on employee morale.Keywords: Work Motivation, Leadership, Employee Morale.